2020
DOI: 10.1111/ijfs.14696
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between lipid and protein oxidation progress in the tail and claw muscles of signal crayfish (Pacifastacus leniusculus)

Abstract: Microbial activity and then oxidation progress are the most important freshness indicators during postmortem. In this study, we monitored proteomic and microbial changes, as well as biochemical degradation, in the tail and claw muscles of crayfish stored for 12 days at +4°C. One specified protein band at 107 kDa in the claw muscle and two specified protein bands in the tail muscle at 140 and 36-40 kDa were identified. Western blotting indicated a higher amount of oxidised proteins in the tail compared to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
3
1
0
Order By: Relevance
“…However, the band intensity at approximately 220 kDa decreased very pronounced in all groups, especially in the unbled group, by elapsed time. This result is in accordance with previous studies [ 33 , 46 ], which reported a decreasing trend in MHC band intensity. Apparently, MHC was not resistant to proteolysis in this study probably due to the formation of cross-linked proteins [ 47 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the band intensity at approximately 220 kDa decreased very pronounced in all groups, especially in the unbled group, by elapsed time. This result is in accordance with previous studies [ 33 , 46 ], which reported a decreasing trend in MHC band intensity. Apparently, MHC was not resistant to proteolysis in this study probably due to the formation of cross-linked proteins [ 47 ].…”
Section: Discussionsupporting
confidence: 94%
“…The decreasing trend of calpain activity in all of the samples over time in the present study is in accordance with previous findings [ 32 , 33 ]. Calpain autolyzes during the proteolytic process and levels decrease therefore concomitantly [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…The findings are consistent with [ 44 ], who observed similar changes in signal crayfish ( Pacifastacus leniusculus ). It should also be noted that there is a link between TBARS levels and protein carbonylation because lipid and protein oxidations occur during frozen storage through a free radical chain reaction.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, oysters are filter feeders. Because of this, oysters accumulate almost all particles that exist in the surrounding water, especially bacteria 16–18 . Therefore, a large number of microorganisms are attached to the oyster's body and internal organs.…”
Section: Introductionmentioning
confidence: 99%